Reference electrode, preparation method thereof and battery

By providing a protective layer composed of nanoinsulating material on the reference electrode, the stability problem caused by the reference electrode contact with the battery cell during the cycle is solved, and a longer service life and a more stable potential reference are achieved.

CN119764323APending Publication Date: 2025-04-04BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411629765.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During the cycle, the reference electrode may be in direct contact with the battery cell system, resulting in side reactions of the active substance and the electrolyte, resulting in degradation of the electrode performance, plating peeling, potential drift and short circuit, resulting in poor stability of the reference electrode.

Method used

A reference electrode design is adopted that includes a main reference electrode and a protective layer disposed on the main reference electrode side. The protective layer consists of nano-insulating material and glue liquid. Metal ions can pass through the protective layer, while electrons cannot pass through, thus forming a barrier that only ions are allowed to pass through, preventing external current from interfering with the potential of the reference electrode.

Benefits of technology

The protective layer effectively isolates the direct contact between the main reference electrode and the electrolyte, prevents side reactions and short circuits, improves the stability of the reference electrode and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764323A_ABST
    Figure CN119764323A_ABST
Patent Text Reader

Abstract

The invention discloses a reference electrode, a preparation method thereof and a battery. Relates to the technical field of batteries and aims to solve the problem of poor stability of a reference electrode. The reference electrode comprises a main reference electrode and a protective layer arranged on one side of the main reference electrode. Wherein metal ions can pass through the protective layer, and electrons cannot pass through the protective layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a reference electrode and a preparation method thereof, and a battery. Background Art

[0002] The reference electrode is an electrode that can provide a stable potential value. It is used as a reference standard in electrochemical measurements and is used in conjunction with other electrodes to calculate the potential of the electrode being measured by measuring the battery voltage. During the cycle of the reference electrode, the reference electrode may be in direct contact with the battery system, causing side reactions between the active substances on the reference electrode and the electrolyte, which may lead to a decrease in electrode performance, resulting in the shedding of the reference electrode coating, potential drift, and short circuits between the reference electrode and the battery cell. These conditions may cause the reference electrode to fail, resulting in poor stability of the reference electrode. Summary of the invention

[0003] The purpose of the present application is to provide a reference electrode and a preparation method thereof, and a battery, in order to solve the problem of poor stability of the reference electrode.

[0004] In order to achieve the above objectives, this application adopts the following technical solutions:

[0005] In a first aspect, the present application provides a reference electrode, which includes: a main reference electrode and a protective layer arranged on one side of the main reference electrode.

[0006] Among them, metal ions can pass through the protective layer, but electrons cannot pass through the protective layer.

[0007] In the protective layer of the reference electrode provided in the embodiment of the present application, metal ions can pass through the protective layer but electrons cannot, so that the protective layer forms a barrier that only allows ions to pass through, which helps to prevent external current from interfering with the reference electrode potential, thereby ensuring that the reference electrode can provide a long-term stable potential reference.

[0008] Moreover, the protective layer of the reference electrode is used to prevent the main reference electrode of the reference electrode from contacting the electrolyte, effectively isolating the direct electron exchange between the main reference electrode and the electrolyte, preventing the main reference electrode from undergoing electrochemical reaction with the electrolyte, reducing the occurrence of shedding of the main reference electrode coating, potential drift, and short circuit between the reference electrode and the battery cell, thereby improving the stability of the reference electrode and extending the service life of the reference electrode.

[0009] In some embodiments, the material of the protection layer includes nano insulating material, and the average particle size of the nano insulating material ranges from 20 nm to 50 nm.

[0010] In some embodiments, the nano insulating material includes at least one of boehmite, silicon dioxide, titanium dioxide, and aluminum oxide.

[0011] In some embodiments, the protective layer includes the following materials in parts by weight: 10 to 30 parts of nano insulating material and 1 to 10 parts of glue.

[0012] In some embodiments, the glue is a first glue, and the material of the first glue includes: polyvinylidene fluoride.

[0013] In some embodiments, the protective layer includes the following mass parts of the first glue: 2 parts to 10 parts.

[0014] In some embodiments, the adhesive is a second adhesive, and the material of the second adhesive includes: styrene-butadiene rubber.

[0015] In some embodiments, the protective layer includes the following weight parts of the second glue: 1 part to 5 parts.

[0016] In some embodiments, the protective layer further comprises the following materials in parts by weight: 2 parts to 10 parts of a binder.

[0017] In some embodiments, the protective layer further comprises the following materials in parts by weight: 0.1 to 1 part of a dispersant.

[0018] In some embodiments, the primary reference electrode includes at least one of a copper wire lithium-plated reference electrode, a lithium alloy reference electrode, a lithium foil reference electrode, and a metal compound reference electrode.

[0019] In some embodiments, the metal compound-containing reference electrode includes at least one of a lithium compound reference electrode, a sodium compound reference electrode, a potassium compound reference electrode, and a magnesium compound reference electrode.

[0020] In some embodiments, the tensile strength of the reference electrode is in the range of 500 kg / cm 2 ~600kg / cm 2 .

[0021] In some embodiments, the electrochemical impedance of the reference electrode ranges from 50 mΩ to 65 mΩ.

[0022] In a second aspect, the present application provides a method for preparing a reference electrode. The method for preparing the reference electrode comprises:

[0023] A protective layer slurry is formed on one side of the main reference electrode.

[0024] The protective layer slurry is dried to form a protective layer, wherein metal ions can pass through the protective layer, but electrons cannot pass through the protective layer.

[0025] It can be understood that the beneficial effects that can be achieved by the method for preparing the reference electrode provided in the above embodiments of the present application can be referred to the beneficial effects of the reference electrode mentioned above, and will not be repeated here.

[0026] In some embodiments, forming a protective layer slurry includes:

[0027] A first glue and a nano insulating material are provided, wherein the material of the first glue includes: polyvinylidene fluoride.

[0028] Add part of the nano insulating material into the first glue solution and stir to form a first solution.

[0029] The remaining part of the nano insulating material is added to the first solution, and then an organic solvent is added and stirred to form a protective layer slurry.

[0030] In some embodiments, forming a protective layer slurry includes:

[0031] A second glue, a binder and a nano insulating material are provided, wherein the material of the second glue includes: styrene-butadiene rubber.

[0032] The binder and the inorganic solvent are mixed and stirred to form a second solution.

[0033] A portion of the nano insulating material is added to the second solution and stirred to form a third solution.

[0034] The remaining portion of the nano insulating material is added to the third solution and stirred to form a fourth solution.

[0035] The second glue solution is added into the fourth solution, and stirred to form a protective layer slurry.

[0036] In some embodiments, the protective layer slurry has a 1S -1 The viscosity of the slurry is in the range of 10000 mPa·s to 20000 mPa·s.

[0037] In some embodiments, the protective layer slurry has a 50S -1 The viscosity of the slurry is in the range of 2000 mPa·s to 5000 mPa·s.

[0038] In a third aspect, the present application provides a battery. The battery comprises: a reference electrode as in any one of the above embodiments and an electrolyte. The protective layer of the reference electrode is used to prevent the main reference electrode of the reference electrode from contacting the electrolyte.

[0039] It can be understood that the beneficial effects that can be achieved by the battery provided in the above embodiments of the present application can refer to the beneficial effects of the reference electrode mentioned above, which will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0041] Figure 1 A flow chart of a reference electrode preparation method provided in an embodiment of the present application;

[0042] Figure 2 Schematic diagram of the reference electrode preparation process of Example 9 and Comparative Example 1 of the present application;

[0043] Figure 3 Graph showing the results of the reference calibration tests of the reference electrodes of Example 9 and Comparative Example 1;

[0044] Figure 4 A constant current and constant voltage charging cycle test result diagram of a three-electrode soft-pack commercial battery made of the reference electrodes of Example 9 and Comparative Example 1;

[0045] Figure 5 Schematic diagram of a three-electrode soft-pack commercial battery made of the reference electrodes of Example 9 and Comparative Example 1;

[0046] Figure 6 A test schematic diagram of a three-electrode soft-pack commercial battery made of the reference electrodes of Example 9 and Comparative Example 1;

[0047] Figure 7 A diagram showing the end of the test of a three-electrode soft-pack commercial battery made of the reference electrode of Example 9;

[0048] Figure 8 Comparison of charge and discharge curves of a three-electrode soft-pack commercial battery made from the reference electrode of Example 9 before and after 450 cycles. DETAILED DESCRIPTION

[0049] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0050] In the description of this application, it should be understood that the terms "upper", "lower", "left", "right", "front", "back", "inside", "outside", etc. indicate directions or positional relationships based on the directions or relative positional relationships shown in the accompanying drawings, and are only for the convenience of describing this application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on this application. Unless otherwise specified, the above-mentioned directional description can be flexibly set in the process of actual application under the condition that the relative positional relationship shown in the accompanying drawings is met.

[0051] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, "plurality" means two or more.

[0052] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection. It can be directly connected, or indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0053] In the present application, the terms "comprises", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, article or device. In the absence of further restrictions, an element defined by the sentence "comprising a ..." does not exclude the presence of other identical elements in the process, article or device including the element.

[0054] In the embodiments of the present application, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.

[0055] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.

[0056] The embodiment of the present application provides a battery, which includes: a reference electrode and an electrolyte.

[0057] The reference electrode plays a vital role in electrochemical measurements. The reference electrode is a type of electrode that maintains a constant electrode potential and is used as a reference for comparison when measuring various electrode potentials. The electrode reaction on the reference electrode must be a single reversible reaction with a stable and reversible electrochemical potential, and the electrode potential must be stable and reproducible.

[0058] The electrolyte contains a solution or molten salt that can conduct ions and provide a channel for ion transfer, allowing electrochemical reactions to occur between electrodes.

[0059] The concentration and activity of ions in the electrolyte can affect the potential of the reference electrode, thereby affecting the potential measurement and reaction process of the entire electrochemical system. Therefore, when conducting potential measurement and electrochemical reaction research, it is necessary to select a suitable reference electrode in the electrolyte to ensure accurate measurement of the potential and the normal progress of the electrochemical process.

[0060] However, the reference electrode has several major disadvantages in terms of cycle life: (1) For the copper wire lithium-plated reference electrode, its cycle life is much lower than the service life of the battery cell. During use, it usually faces problems such as side reactions between the lithium plating layer and the electrolyte, and the lithium plating layer falling off. (2) Lithium alloy references are usually expensive, and the potential value changes with the lithium content and the current passing through the reference. During the cycle, there will be problems such as potential drift and side reactions between the surface lithium and the electrolyte. (3) For the reference electrode prepared by coating the active material on the current collector, the current collector includes metal wires and metal foils. During the cycle, there will be short circuit problems, resulting in failure of the reference electrode. In other words, during the cycle of the reference electrode, the reference electrode may be in direct contact with the battery system, causing the active material on the reference electrode to react with the electrolyte, which may lead to a decrease in electrode performance, resulting in the frequent occurrence of reference electrode plating falling off, potential drift, and short circuit between the reference electrode and the battery cell, which may cause the reference electrode to fail, resulting in poor stability of the reference electrode.

[0061] Based on this, an embodiment of the present application provides a reference electrode, which includes: a main reference electrode and a protective layer arranged on one side of the main reference electrode.

[0062] Among them, metal ions can pass through the protective layer, but electrons cannot pass through the protective layer.

[0063] The main function of the reference electrode is to provide a stable potential reference. When metal ions can pass through the protective layer but electrons cannot, the protective layer forms a barrier that only allows ions to pass through, which helps prevent external current from interfering with the reference electrode potential, thereby ensuring that the reference electrode can provide a long-term stable potential reference.

[0064] Moreover, the protective layer of the reference electrode is used to prevent the main reference electrode of the reference electrode from contacting the electrolyte, effectively isolating the direct electron exchange between the main reference electrode and the electrolyte, preventing the main reference electrode from undergoing electrochemical reaction with the electrolyte, reducing the occurrence of shedding of the main reference electrode coating, potential drift, and short circuit between the reference electrode and the battery cell, thereby improving the stability of the reference electrode and extending the service life of the reference electrode.

[0065] In some embodiments, the material of the protection layer includes nano insulating material, and the average particle size of the nano insulating material ranges from 20 nm to 50 nm.

[0066] For example, the average particle size of the nano insulating material may be 20 nm, 30 nm, 40 nm or 50 nm, etc., which is not limited here.

[0067] It can be understood that the transmission of electrons requires sufficient conductive channels or free electrons in the material of the protective layer, but the nano-insulating material cannot form free electrons due to its high resistivity and dense microstructure, which effectively blocks the transmission path of electrons, making the nano-insulating material form a dense and uniform film that electrons cannot pass through; metal ions are easily affected by the material structure and porosity of the protective layer, so by setting the average particle size of the nano-insulating material in the range of 20nm to 50nm, the protective layer has porosity and channel structure, which can enable metal ions to be transmitted through the pores and channel structure.

[0068] In some embodiments, the nano insulating material includes at least one of boehmite, silicon dioxide, titanium dioxide, and aluminum oxide.

[0069] Boehmite has excellent electrical insulation and heat resistance. Its molecular structure enables boehmite to effectively prevent the free flow of electrons, thus exhibiting high insulation properties.

[0070] Silicon dioxide has excellent insulating properties.

[0071] Titanium dioxide has good insulating properties and is used as an electrical insulating material.

[0072] Alumina has the advantages of high dielectric strength, low dielectric constant and good heat resistance, and has good insulation properties, mechanical properties and chemical stability.

[0073] Therefore, at least one of nano insulating materials such as boehmite, silicon dioxide, titanium dioxide and aluminum oxide, as the material of the protective layer, can prevent electrons from passing through the protective layer.

[0074] In some embodiments, the protective layer includes the following materials in parts by weight: 10 to 30 parts of nano insulating material and 1 to 10 parts of glue.

[0075] Exemplarily, the nano insulating material may be 10 parts, 15 parts, 20 parts, 25 parts or 30 parts, etc., which is not limited here.

[0076] Exemplarily, the glue solution can be 1 part, 3 parts, 5 parts, 7 parts or 10 parts, etc., which is not limited here.

[0077] The protective layer contains 10 to 30 parts of nano-insulating materials, such as nano-silicon dioxide (SiO2) or nano-TiO2. The small size effect and macroscopic quantum tunneling effect of the nano-materials enable them to interact with the electron clouds of unsaturated bonds in other materials, and then combine with the macromolecules in the glue to form a three-dimensional network structure. Not only does the nano-insulating material itself have excellent insulating properties and can effectively isolate current conduction, it also improves the strength, toughness, and ductility of the material, and gives the material extremely strong corrosion resistance and oxidation resistance.

[0078] 1 to 10 parts of glue in the protective layer can firmly bond the nano insulating materials together, fill the gaps between the nano insulating materials, and control the viscosity and fluidity of the protective layer to form a stable and continuous protective layer, thereby improving the overall performance and durability of the protective layer.

[0079] In some embodiments, the glue is a first glue, and the material of the first glue includes: polyvinylidene fluoride.

[0080] Polyvinylidene fluoride (PVDF) glue can provide good adhesion, ensuring close bonding between the nano-insulating material and the substrate, thereby improving the overall strength and stability of the protective layer; PVDF glue has excellent weather resistance and wear resistance, and can resist the erosion of the protective layer by harsh environments (such as high temperature, humidity, ultraviolet rays, etc.), thereby extending its service life.

[0081] The combination of nano-insulating material and PVDF adhesive can bring out the synergistic effect of the two to further improve the insulation performance, weather resistance and wear resistance of the protective layer; and by adjusting the ratio of nano-insulating material and PVDF adhesive, the performance of the protective layer can be optimized according to specific application requirements to achieve customized protection effects.

[0082] In some embodiments, the protective layer includes the following mass parts of the first glue: 2 parts to 10 parts.

[0083] Exemplarily, the first glue solution can be 2 parts, 4 parts, 6 parts, 8 parts or 10 parts, etc., which is not limited here.

[0084] Through the above settings, the overall performance and durability of the protective layer can be further improved.

[0085] In some embodiments, the adhesive is a second adhesive, and the material of the second adhesive includes: styrene-butadiene rubber.

[0086] Styrene butadiene rubber provides good elasticity and adhesion for the protective layer. Styrene butadiene rubber is a synthetic rubber with good comprehensive performance, high wear resistance, tensile strength and processing performance. In the protective layer, styrene butadiene rubber can be closely combined with nano insulating materials to form a strong bonding layer, ensuring the stability and durability of the protective layer. In addition, the elasticity of styrene butadiene rubber also helps to alleviate external shocks and vibrations, and plays a buffering role for the materials under the protective layer.

[0087] In some embodiments, the protective layer includes the following weight parts of the second glue: 1 part to 5 parts.

[0088] Exemplarily, the second glue solution can be 1 part, 2 parts, 3 parts, 4 parts or 5 parts, etc., which is not limited here.

[0089] Through the above arrangement, the bonding performance and stability of the protective layer can be improved.

[0090] In some embodiments, the protective layer further comprises the following materials in parts by weight: 2 parts to 10 parts of a binder.

[0091] For example, the binder may be 2 parts, 4 parts, 6 parts, 8 parts or 10 parts, etc., which is not limited here.

[0092] Exemplarily, the binder may be carboxymethyl cellulose.

[0093] It can be understood that the binder can further enhance the adhesion between the second glue and the nano insulating material, and improve the stability and durability of the protective layer.

[0094] In some embodiments, the protective layer further comprises the following materials in parts by weight: 0.1 to 1 part of a dispersant.

[0095] For example, the dispersant may be 0.1 part, 0.2 part, 0.5 part, 0.7 part or 1 part, etc., and is not limited here.

[0096] It can be understood that adding 0.1 to 1 part of dispersant into the protective layer can reduce the agglomeration of particles and improve the uniformity of the film layer of the protective layer.

[0097] In some embodiments, the primary reference electrode includes at least one of a copper wire lithium-plated reference electrode, a lithium alloy reference electrode, a lithium foil reference electrode, and a metal compound reference electrode.

[0098] It can be understood that at least one of the above-mentioned copper wire lithium-plated reference electrode, lithium alloy reference electrode, lithium foil reference electrode and metal compound reference electrode as the main reference electrode can reduce the occurrence of shedding of the main reference electrode coating, potential drift and short circuit between the reference electrode and the battery cell, improve the stability of the reference electrode, and thus extend the service life of the reference electrode.

[0099] In some embodiments, the metal compound reference electrode includes at least one of a lithium compound reference electrode, a sodium compound reference electrode, a potassium compound reference electrode, and a magnesium compound reference electrode. It can be understood that the above configuration can expand the application of the reference electrode to metal ion batteries such as lithium ion batteries, sodium ion batteries, potassium ion batteries, and magnesium ion batteries, thereby expanding the scope of use of the reference electrode.

[0100] In some embodiments, the tensile strength of the reference electrode is in the range of 500 kg / cm 2 ~600kg / cm 2 .

[0101] For example, the tensile strength of the reference electrode can be 500 kg / cm 2 、520kg / cm 2 、540kg / cm 2 、560kg / cm 2 nm, 580kg / cm 2 or 600kg / cm 2 Etc., there is no limitation here.

[0102] The above settings indicate that the maximum stress range that the reference electrode can withstand in the tensile test is 500 kg / cm 2 ~600kg / cm 2 , with good mechanical properties.

[0103] In some embodiments, the electrochemical impedance of the reference electrode ranges from 50 mΩ to 65 mΩ.

[0104] For example, the electrochemical impedance of the reference electrode may be 50 mΩ, 52 mΩ, 54 mΩ, 56 mΩ, 58 mΩ or 60 mΩ, etc., which is not limited here.

[0105] The above configuration shows that the electrochemical impedance of the reference electrode is small (compared to the case where there is only the main reference electrode, the electrochemical impedance of the main reference electrode is 55 mΩ, indicating that the protective layer has little effect on the electrochemical performance of the reference electrode.

[0106] The embodiments of the present application provide a method for preparing a reference electrode. Figure 1 As shown, the preparation method of the reference electrode includes: S1-S2.

[0107] S1: forming a protective layer slurry on one side of the main reference electrode.

[0108] S2: After the protective layer slurry is dried, a protective layer is formed, wherein metal ions can pass through the protective layer, but electrons cannot pass through the protective layer.

[0109] In some embodiments, S1 forms a protective layer slurry including: S1.1A to S1.3A.

[0110] S1.1A: Provide a first glue and a nano insulating material, wherein the material of the first glue includes: polyvinylidene fluoride.

[0111] S1.2A: Add part of the nano insulating material to the first glue solution and stir to form a first solution.

[0112] S1.3A: Add the remaining portion of the nano insulating material to the first solution, then add the organic solvent, and stir to form a protective layer slurry.

[0113] Exemplarily, for the main reference electrode which is sensitive to air and whose active material is a reference electrode prepared by coating a current collector with a lithium iron phosphate or lithium titanate-based lithium-containing compound, a copper wire lithium reference electrode, a lithium alloy reference electrode, and a lithium foil reference electrode, the main reference electrode can be further expanded to be a sodium metal reference, a potassium metal reference, etc. The material of the first colloid can be polyvinylidene fluoride, and the protective layer slurry S1 is prepared by the above S1.1A to S1.3A.

[0114] Exemplarily, for the copper wire lithium-plated reference electrode, since lithium is sensitive to the air environment, it needs to be carried out in a glove box. The method for making the copper wire lithium-plated reference electrode includes but is not limited to: (1) After the copper wire is placed in the battery cell, the copper wire is plated with lithium using the positive and negative electrodes; (2) The copper wire is dipped in molten lithium to directly form a metal reference with a lithium layer; (3) The copper wire is coated with a layer of metal lithium foil or other forms of copper wire lithium-plated reference, with the copper wire as the reference current collector and the lithium metal layer as the reference active material. The copper wire lithium-plated reference is usually a linear cylinder, because the reference is placed in a container containing a protective layer slurry of the first glue solution, and after standing for a while and taking it out, with the help of the glue solution components, the protective layer slurry will adhere to the outermost layer of the copper wire lithium-plated reference, and after the organic solvent evaporates, a dense and stable protective layer will form on the outside.

[0115] In some embodiments, S1 forms a protective layer slurry including: S1.1B to S1.5B.

[0116] S1.1B: Provide a second glue, a binder and a nano insulating material, wherein the material of the second glue includes: styrene-butadiene rubber.

[0117] S1.2B: Mix the binder and the inorganic solvent and stir to form a second solution.

[0118] S1.3B: Add part of the nano insulating material to the second solution and stir to form a third solution.

[0119] S1.4B: Add the remaining portion of the nano insulating material to the third solution and stir to form a fourth solution.

[0120] S1.5B: Add the second glue solution to the fourth solution and stir to form a protective layer slurry.

[0121] For example, for a foil-like sheet reference electrode, a protective layer slurry formed by S1.1A to S1.3A or a protective layer slurry formed by S1.1B to S1.5B may be directly coated on the outer layer of the main reference electrode, and then dried to form a protective layer.

[0122] Exemplarily, for metal wire reference electrodes, a dipping method can be used, and the protective layer slurry will adhere to the outermost layer. If the adhesion is weak, the glue content in the formula can be optimized. Here, this method can be further expanded to reference electrodes containing metal compounds (such as sodium compounds such as sodium vanadium phosphate). The reference electrode is placed in the battery cell to form a three-electrode battery, in which the reference electrode containing the metal compound can be prepared under ambient conditions, and no additional equipment is required for mass production.

[0123] In some embodiments, the protective layer slurry 1S -1 The viscosity of the slurry is in the range of 10000 mPa·s to 20000 mPa·s.

[0124] For example, the protective layer slurry 1S -1 The viscosity of the slurry may be 10000 mPa·s, 12000 mPa·s, 14000 mPa·s, 16000 mPa·s, 18000 mPa·s or 20000 mPa·s, etc., but is not limited thereto.

[0125] In some embodiments, the protective layer slurry 50S -1 The viscosity of the slurry is in the range of 2000 mPa·s to 5000 mPa·s.

[0126] For example, protective layer slurry 50S -1 The viscosity of the slurry may be 2000 mPa·s, 2500 mPa·s, 3000 mPa·s, 3500 mPa·s, 4000 mPa·s or 5000 mPa·s, etc., but is not limited thereto.

[0127] It can be understood that the above-mentioned viscosity range of the protective layer slurry can make the protective layer slurry have better fluidity, which is helpful to form a uniform protective layer.

[0128] The present application is further described in detail below by taking several specific experiments as examples.

[0129] Example 1

[0130] Embodiment 1 provides a reference electrode, and the preparation method of the reference electrode is as follows:

[0131] R1: Coat a layer of lithium iron phosphate slurry on aluminum foil and dry it to form an aluminum foil lithium iron phosphate main reference electrode.

[0132] R2: A protective layer slurry is formed on one side of the main reference electrode; the protective layer slurry includes aluminum oxide, carboxymethyl cellulose, styrene butadiene rubber, dispersant and water in a mass ratio of 90:8:3:1.05:500, wherein the sum of the mass of aluminum oxide, carboxymethyl cellulose, styrene butadiene rubber and dispersant and the mass ratio of the protective layer slurry is 0.182; the surface density of the protective layer slurry is 0.46 mg / cm 2 .

[0133] R3: Dry the protective layer slurry to form a protective layer.

[0134] Example 2

[0135] Example 2 provides a reference electrode. The preparation method of the reference electrode is the same as that of Example 1, except that the surface density of the protective layer slurry in Example 2 is 0.68 mg / cm 2 .

[0136] Example 3

[0137] Example 3 provides a reference electrode. The preparation method of the reference electrode is the same as that of Example 1, except that the surface density of the protective layer slurry in Example 3 is 0.9 mg / cm 2 .

[0138] Example 4

[0139] Example 4 provides a reference electrode. The preparation method of the reference electrode is the same as that of Example 1, except that the surface density of the protective layer slurry of Example 4 is 1.19 mg / cm 2 .

[0140] Example 5

[0141] Example 5 provides a reference electrode. The preparation method of the reference electrode is the same as that of Example 1, except that the ratio of the sum of the mass of aluminum oxide, carboxymethyl cellulose, styrene-butadiene rubber and dispersant to the mass of the protective layer slurry is 0.21; the surface density of the protective layer slurry is 0.47 mg / cm 2 .

[0142] Example 6

[0143] Example 6 provides a reference electrode. The preparation method of the reference electrode is the same as that of Example 1, except that the surface density of the protective layer slurry in Example 6 is 0.52 mg / cm 2 .

[0144] Example 7

[0145] Example 7 provides a reference electrode. The preparation method of the reference electrode is the same as that of Example 1, except that the surface density of the protective layer slurry in Example 7 is 0.84 mg / cm 2 .

[0146] Example 8

[0147] Example 8 provides a reference electrode. The preparation method of the reference electrode is the same as that of Example 1, except that the surface density of the protective layer slurry in Example 8 is 1.23 mg / cm 2 .

[0148] Example 9

[0149] Example 9 provides a reference electrode, and the preparation method of the reference electrode is as follows:

[0150] Q1: Provide aluminum wire lithium iron phosphate primary reference electrode.

[0151] Q2: A protective layer slurry is formed on one side of the main reference electrode; the protective layer slurry includes aluminum oxide, carboxymethyl cellulose, styrene butadiene rubber, a dispersant and water in a mass ratio of 90:8:3:1.05:500, wherein the sum of the masses of aluminum oxide, carboxymethyl cellulose, styrene butadiene rubber and the dispersant and the mass ratio of the protective layer slurry is 0.182; the surface density of the protective layer slurry is 0.46 mg / cm 2 .

[0152] Q3: The protective layer slurry is dried to form a protective layer.

[0153] Example 10

[0154] Example 10 provides a reference electrode, and the preparation method of the reference electrode is the same as that of Example 9, except that the main reference electrode is aluminum wire lithium iron phosphate.

[0155] Embodiment 11

[0156] Example 11 provides a reference electrode, and the preparation method of the reference electrode is the same as that of Example 9, except that the main reference electrode is aluminum foil lithium iron titanate.

[0157] Comparative Example 1

[0158] Comparative Example 1 provides a reference electrode, which is aluminum foil lithium iron phosphate.

[0159] Comparative Example 2

[0160] Comparative Example 2 provides a reference electrode, which is copper wire cross-linked with lithium.

[0161] Comparative Example 3

[0162] Comparative Example 3 provides a reference electrode, which is aluminum wire lithium iron phosphate.

[0163] Comparative Example 4

[0164] Comparative Example 4 provides a reference electrode, which is aluminum foil lithium iron titanate.

[0165] Performance Testing

[0166] 1. The viscosity of the protective layer slurry of the reference electrodes of Examples 1 to 9 and Comparative Example 1 was tested, and the coating state and cracking state of the main reference electrode were observed. The peeling force, tension, tensile strength and electrochemical impedance of the main reference electrode were tested. The results are shown in Table 1.

[0167] Table 1 Test results of Examples 1 to 9 and Comparative Example 1

[0168]

[0169]

[0170] like Figure 2 As shown, the reference electrodes of Example 9 and Comparative Example 1 were prepared, and then the reference electrodes of Example 9 and Comparative Example 1 were made into a three-electrode soft-pack commercial battery, such as Figure 5 As shown, the battery includes a positive electrode 10, a negative electrode 20, a separator 30 and a reference electrode 40. The lithium iron phosphate and graphite system is assembled using a lamination process, with a total of 12 positive electrode layers and 13 negative electrode layers, and a designed capacity of 2.387Ah. The reference electrode of Example 9 and Comparative Example 1 is placed between the 6th positive electrode layer and the 7th negative electrode layer.

[0171] 2. Reference calibration test: Place the three-electrode soft-pack commercial battery made of the reference electrodes of Example 9 and Comparative Example 1 on a Maccor test cabinet, with the positive electrode 10 and the negative electrode 20 of the battery corresponding to the positive and negative electrodes of the test cabinet, and adjust the battery to 50% SOC (remaining power or charge and discharge state of the battery). Let the battery stand until it returns to the equilibrium voltage, then connect the reference electrode 40 to the positive electrode of the test cabinet, and the negative electrode 20 to the negative electrode of the test cabinet to form a loop of the reference electrode and the negative electrode, set the charge and discharge steps, and adjust the potential of the reference electrode of Comparative Example 1 to 50% SOC. The results are as follows: Figure 3 shown.

[0172] Figure 3 This is a graph of the reference calibration test results of the reference electrodes of Example 9 and Comparative Example 1. The three-electrode soft-pack commercial batteries made of the reference electrodes of Example 9 and Comparative Example 1 both have obvious charge and discharge characteristics of lithium iron phosphate on graphite, and the potential has a significantly longer platform area at around 50% SOC, which indicates that the protective layer of the reference electrode of Example 9 will not affect the electrochemical characteristics of the reference electrode and will not change the standard potential of the reference electrode.

[0173] 3. Life Acceleration Test: The three-electrode soft-pack commercial battery made of the reference electrodes of Example 9 and Comparative Example 1 was placed in an incubator set at 45°C. Figure 6 As shown, it is placed on the blue electric test cabinet, and the positive electrode 10 and negative electrode 20 of the battery correspond to the positive electrode 10 and negative electrode 20 of the test cabinet. The negative electrode 20 is connected to the positive electrode of the auxiliary voltage line of the test cabinet, and the reference electrode 40 is connected to the negative electrode of the auxiliary voltage line of the test cabinet, forming a voltage monitoring circuit between the reference electrode 40 and the negative electrode. The battery cycle process is set to charge at 0.5C constant current and constant voltage to 3.65V, 0.02C current cutoff (1C = 2.387A, 1C means that the battery takes 1 hour to be fully charged), discharge at 0.5C constant current discharge, 2V voltage cutoff, and cycle 450 times. The results are as follows Figure 4 and Figure 8 shown.

[0174] Figure 4 The constant current and constant voltage charging cycle test result of the three-electrode soft-pack commercial battery made of the reference electrode of Example 9 is shown in FIG. The capacity retention rate of the three-electrode soft-pack commercial battery made of the reference electrode of Example 9 is 94%, and the conventional capacity decay curve during the battery cycle process, wherein the graphite potential curve has no significant abnormality, such as Figure 7 As shown in the figure, after 450 cycles, the capacity retention rate of the three-electrode soft-pack commercial battery made of the reference electrode of Example 9 was 94%. The photo of the state at the end of the test showed that the battery did not fail due to bulging or bloating. Figure 8 As shown in FIG. 1 , the charge and discharge curves of the three-electrode soft-pack commercial battery made of the reference electrode of Example 9 are compared before and after 450 cycles. The curves are almost overlapped, indicating that the battery mainly loses non-polarization capacity during the cycle, that is, the consumption of active lithium. Figure 4 As shown, the capacity retention rate of the three-electrode soft-pack commercial battery made of the reference electrode of Comparative Example 1 is 94%, and the conventional capacity decay curve during the battery cycle is shown. However, at the 90,000th minute of the test, the graphite potential moves up, and at the 120,000th minute, the voltage rises sharply, indicating that the reference electrode of Comparative Example 3 may be in contact with the graphite, resulting in a local short circuit and an increase in voltage. Therefore, the service life of the reference electrode of Comparative Example 3 is less than 90,000 minutes (62.5 days), and the test life of the cycle at 45°C and 0.5C is 300 cycles.

[0175] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A reference electrode, characterized in that include: A main reference electrode and a protective layer disposed on one side of the main reference electrode; Wherein, metal ions can pass through the protective layer, but electrons cannot pass through the protective layer.

2. The reference electrode according to claim 1, characterized in that The material of the protective layer includes nano insulating material, and the average particle size of the nano insulating material ranges from 20nm to 50nm.

3. The reference electrode according to claim 2, characterized in that The nano insulating material comprises at least one of boehmite, silicon dioxide, titanium dioxide and aluminum oxide.

4. The reference electrode according to claim 2, characterized in that The protective layer includes the following materials in parts by weight: 10 to 30 parts of the nano insulating material and 1 to 10 parts of glue.

5. The reference electrode according to claim 4, characterized in that The glue is a first glue, and the material of the first glue includes: polyvinylidene fluoride.

6. The reference electrode according to claim 5, characterized in that The protective layer includes the following mass parts of the first glue solution: 2 parts to 10 parts.

7. The reference electrode according to claim 4, characterized in that The adhesive is a second adhesive, and the material of the second adhesive includes: styrene-butadiene rubber.

8. The reference electrode according to claim 7, characterized in that The protective layer includes the following mass parts of the second glue solution: 1 part to 5 parts.

9. The reference electrode according to claim 7, characterized in that The protective layer further comprises the following materials in parts by weight: 2 parts to 10 parts of a binder.

10. The reference electrode according to claim 9, characterized in that The protective layer further comprises the following materials in parts by weight: 0.1 to 1 part of a dispersant.

11. The reference electrode according to claim 1, characterized in that The main reference electrode comprises: at least one of a copper wire lithium-plated reference electrode, a lithium alloy reference electrode, a lithium foil reference electrode and a metal compound reference electrode.

12. The reference electrode according to claim 11, characterized in that The metal compound-containing reference electrode includes at least one of a lithium compound reference electrode, a sodium compound reference electrode, a potassium compound reference electrode and a magnesium compound reference electrode.

13. The reference electrode according to any one of claims 1 to 12, characterized in that The tensile strength of the reference electrode is in the range of 500 kg / cm 2 ~600kg / cm 2 .

14. The reference electrode according to any one of claims 1 to 12, characterized in that The electrochemical impedance of the reference electrode ranges from 50 mΩ to 65 mΩ.

15. A method for preparing a reference electrode, characterized in that: include: forming a protective layer slurry on one side of the main reference electrode; The protective layer slurry is dried to form a protective layer, wherein metal ions can pass through the protective layer, but electrons cannot pass through the protective layer.

16. The method for preparing a reference electrode according to claim 15, characterized in that: The protective layer slurry comprises: Providing a first glue and a nano insulating material, wherein the material of the first glue comprises: polyvinylidene fluoride; Adding part of the nano insulating material to the first glue solution and stirring to form a first solution; The remaining part of the nano insulating material is added to the first solution, and then an organic solvent is added and stirred to form the protective layer slurry.

17. The method for preparing a reference electrode according to claim 15, characterized in that: The protective layer slurry comprises: Providing a second glue, a binder and a nano insulating material, wherein the material of the second glue comprises: styrene-butadiene rubber; Mixing the binder and the inorganic solvent and stirring to form a second solution; adding part of the nano insulating material to the second solution and stirring to form a third solution; adding the remaining portion of the nano insulating material to the third solution and stirring to form a fourth solution; The second glue solution is added into the fourth solution and stirred to form the protective layer slurry.

18. The method for preparing a reference electrode according to claim 15, characterized in that: The protective layer slurry 1S -1 The viscosity of the slurry is in the range of 10000 mPa·s to 20000 mPa·s; and / or, 50S of the protective layer slurry -1 The viscosity of the slurry is in the range of 2000 mPa·s to 5000 mPa·s.

19. A battery, characterized in that: include: The reference electrode according to any one of claims 1 to 14; The protective layer of the reference electrode is used to prevent the main reference electrode of the reference electrode from contacting the electrolyte.